Remote cortical atrophy and language outcomes after chronic left subcortical stroke with aphasia - Tang, Huijia; Fan, Shuhan; Niu, Xingyang; Li, Zhuhao; Xiao, Peiyi; Zeng, Jinsheng; Xing, Shihui (Frontiers in Neuroscience, 2022)
Objective: Subcortical stroke can cause a variety of language deficits. However, the neural mechanisms underlying subcortical aphasia after stroke remain incompletely elucidated. We aimed to determine the effects of distant cortical structures on aphasia outcomes and examine the correlation of cortical thickness measures with connecting tracts integrity after chronic left subcortical stroke. Methods: Thirty-two patients and 30 healthy control subjects underwent MRI scanning and language assessment with the WAB-R subtests. Among patients, the cortical thickness in brain regions that related to language performance were assessed by the FreeSurfer software. Fiber tracts connecting the identified cortical regions to stroke lesions were reconstructed to determine its correlations with the cortical thickness measures across individual patient. Results: Cortical thickness in different parts of the left fronto-temporo-parietal regions were positively related to auditory-verbal comprehension, spontaneous speech and naming/word finding abilities when controlling for key demographic variables and lesion size (all p < 0.05). Cortical thickness decline in the identified cortical regions was positively correlated with integrity loss of fiber tracts connected to stroke lesions (all p < 0.05). Additionally, no significant difference in cortical thickness was found across the left hemisphere between the subgroup of patients with hypoperfusion and those without hypoperfusion at stroke onset. Conclusions: These findings suggest that remote cortical atrophy independently predicts language outcomes in chronic left subcortical stroke with aphasia and that cortical thinning in these regions might relate to integrity loss of fiber tracts connected to stroke lesions.